Pengembangan Potensi Komoditas Mawar sebagai Kreasi Berkelanjutan pada Aspek Ekonomi Kreatif Desa Karangpring - Bayu Aprillianto; Yosefa Sayekti; Indah Purnamawati; Ririn Irmadariyani; Adhelia Febriana Putri; Alvi Rahmadani; Theodicy Kristian Pratama; Brillian Farel Adhani; Zevicha Angelita Berlian Maskur; Nor Mazlina Abu Bakar (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Rose cultivation in Karangpring Village, Jember Regency, has long been trapped in a low-value commodity chain — sold as fresh cut flowers for grave ceremonies, with farmers earning well below the regional minimum wage. This community service program addresses that gap by applying a creative economy approach to transform raw rose commodities into marketable food and non-food products, including rose syrup, rose jam, bakpia, reed diffusers, and aromatherapy candles. The program was carried out through Focus Group Discussions (FGD), hands-on production training, and structured mentoring sessions with the Women Farmers Community (Kelompok Wanita Tani), covering product development, brand identity, and digital marketing through platforms such as Shopee and Instagram. Beyond product diversification, the program pursued a broader objective: building a self-sustaining creative economy community under village government oversight, capable of managing production, distribution, and market expansion independently. Outcomes indicate a positive shift in community capacity, with consistent participation across five to ten sessions and early market traction through repeat orders at the local level. The program also contributes to the Sustainable Development Goals (SDGs), particularly in the areas of economic welfare, commodity literacy, and responsible resource use. Scaling this initiative from a community unit to a full creative industry will require strategic investment and partnership — a challenge that remains open.